"Once you've been there, you're always recovering": exploring experiences, outcomes, and benefits of substance misuse recovery. Issue 1 (7th March 2016) - Timpson, Hannah; Eckley, Lindsay; Sumnall, Harry; Pendlebury, Marissa; Hay, Gordon
Abstract : Purpose: – Recovery is a central component of UK substance misuse policy, however, relatively little is known about the views and meanings of recovery by those experiencing it. The purpose of this paper is to explore these factors, and understand how service user experiences align to current understandings of "recovery capital". Design/methodology/approach: – This paper draws on qualitative interviews with 32 individuals from six UK recovery communities, including those commissioned by a statutory service ( n =8) and a peer-led recovery community ( n =24). Findings: – Meanings of recovery differed between people in abstinence-based communities and those not; however, all had consistent views on their own recovery outcomes and the benefits they believed recovery brought. All viewed recovery as a process; a continuous journey with no end-point. Internal motivation, peer support, social networks and daily structure were integral to supporting individuals achieve and maintain recovery. Key benefits of recovery reflected recovery capital and included positive relationships, sense of belonging, increased self-worth and confidence, employment and education. Research limitations/implications: – This research shows that recovery experiences and outcomes are not centred entirely on the individual but are wider, more holistic. Maintaining recovery involves being connected to themselves and to the wider environment: family, friends, peers and society. Although the recovery capital model has many elements that were discussed by the participants of this research, the discourse they used does not align with the model. To validly measure and quantify recovery outcomes, individuals need to identify with the measures themselves. Practical implications: – From policy and commissioning perspectives, these findings suggest benefits of recovery that were viewed by participants as indicators of success: demonstrate elements which support recovery; and highlight key social value outcomes which people attribute to recovery. Social implications: – These "softer", qualitative benefits should be considered by policy-makers, commissioners, statutory and non-statutory services in order to evidence outcomes. However, it should also be recognised that a temporally static approach to assessing recovery may be in contradiction to the meaning and perspectives held by those in recovery communities who conceptualise it as a long term and ongoing process. Originality/value: – This paper adds to understandings of experiences and meanings of recovery, with a particular focus on the measurement of outcomes and their meanings, and the role of abstention and continued drug use within the recovery process.